The democratic dilemma : reforming Canada's Supreme Court - Verrelli, Nadia, 1975- (Queen's policy studies., 2013)
The process used to select judges of the Supreme Court of Canada has provoked criticism from the start. Some observers argue the process - where the prime minister has unfettered discretion - suffers from a democratic deficit, but there is also disagreement regarding alternative methods of selection. This book explores the institutional features of the Court, whether the existing process used to select judges ought to be reformed, the overall legitimacy of the Court, as well as the selection and appointment processes of Supreme Court justices in other liberal democracies.